Caveolae-mediated Endocytosis of Intratracheally Instilled Gold Colloid Nanoparticles at the Air–Blood Barrier in Mice. (April 2013) - Naota, Misaki; Shimada, Akinori; Morita, Takehito; Yamamoto, Yuko; Inoue, Kenichiro; Takano, Hirohisa
Endocytosis is the primary mechanism by which nanoparticles are translocated over the alveolar epithelium. The purpose of this study was to elucidate the association between endocytosis and the translocation of nanoparticles at the air–blood barrier (ABB). Gold colloid particles (diameter, 20 nm) were intratracheally instilled into male ICR mice. Fifteen minutes after instillation, localized accumulation of agglomerated gold particles was observed in the cytoplasm of macrophages, on the surface of alveolar epithelial cells (AECs), and in alveoli. Electron microscopy revealed particles in the vesicles of macrophages, on the surface of AECs, and in caveolae-like vesicles in type 1 AECs. Immunohistochemistry demonstrated positive immunolabeling for caveolin-1 in the ABB of untreated lungs as well as lungs treated with gold particles. Double immunofluorescence and immunoelectron microscopy revealed the presence of caveolin-1 in AECs in the untreated lungs. These results suggest that instilled gold colloid particles are internalized into the alveolar epithelium at the ABB by caveolae-mediated endocytosis, which is regarded as a physiological function of AECs.